2012
DOI: 10.1039/c1cc11300c
|View full text |Cite
|
Sign up to set email alerts
|

Tambjamine alkaloids and related synthetic analogs: efficient transmembrane anion transporters

Abstract: The tambjamine alkaloids and related synthetic analogs are potent transmembrane anion tranporters promoting bicarbonate/chloride exchange in model phospholipid liposomes and discharging pH gradients in living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 38 publications
3
49
0
2
Order By: Relevance
“…21 By contrast, currently no anionophore has been identified with strong Cl À > H + /OH À selectivity. 22 Indeed, prodigiosin, 14,15 and some of the most powerful synthetic anionophores, [23][24][25][26][27] have been shown to uncouple vacuolar type H + -ATPase (V-ATPase) and neutralize acidic cellular organelles (such as the Golgi apparatus, lysosomes, and endosomes) by facilitating H + /Cl À symport or Cl À /OH À antiport through organelle membranes. Monensin is also known to exhibit this neutralization effect by promoting Na + /H + antiport through organelle membranes.…”
Section: Introductionmentioning
confidence: 99%
“…21 By contrast, currently no anionophore has been identified with strong Cl À > H + /OH À selectivity. 22 Indeed, prodigiosin, 14,15 and some of the most powerful synthetic anionophores, [23][24][25][26][27] have been shown to uncouple vacuolar type H + -ATPase (V-ATPase) and neutralize acidic cellular organelles (such as the Golgi apparatus, lysosomes, and endosomes) by facilitating H + /Cl À symport or Cl À /OH À antiport through organelle membranes. Monensin is also known to exhibit this neutralization effect by promoting Na + /H + antiport through organelle membranes.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently synthesized novel synthetic tambjamine analogues bearing aromatic substituents in the enamine moiety, as well as explored different substitution patterns on characteristic alkoxy group of the central pyrrole ring. These compounds proved to be very efficient anion exchangers in liposome models, promoting both chloride and bicarbonate transport [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…They contain bipyrrole core and, like other natural and semi- synthetic acyclic anion receptors have received increasing attention as anion carriers in recent years [97,99]. Tambjamines are typically easier to prepare than the prodigiosins and generally possess higher p K a values (i.e., p K a ≈ 10 vs. 7.2, for tambjamines and prodigiosins, respectively); thus, unlike prodigiosins, tambjamines remain largely protonated at physiological pH.…”
Section: Prodigiosin- Tambjamine- and Perenosin-based Anion Recepmentioning
confidence: 99%
“…Quesada and coworkers described transmembrane anion transport studies of the tambjamine alkaloid derivative 44a and reported that these compounds are potent anion transporters capable of effecting NO 3 − /Cl − and HCO 3 /Cl − exchange in liposomes at low concentrations [99]. The lower intracellular pH levels observed in vitro correlated with antitumor activity in the human melanoma (A375) and human mammary epithelial (MCF-10A) cell lines.…”
Section: Prodigiosin- Tambjamine- and Perenosin-based Anion Recepmentioning
confidence: 99%